Effects of nitrogen application and tillage on maize (Zea mays L.) yield, nitrogen use efficiency, and nutrient stocks under contrasting soils - Ashenafi Nigussie (Agrosystems, Geosciences & Environment, 2025)
Abstract In the Central Rift Valley of Ethiopia, enhancing fertilizer efficiency and maize yields on smallholder farms is a pressing issue, especially given the challenges of low soil fertility. To address this, field experiments were carried out over two consecutive years (2019–2020) under rain‐fed conditions with the aim to assess short‐term effects of nitrogen application and tillage methods on nutrient stocks, yields, and nitrogen use efficiency of maize grown in two different soil types (STs): Cambisols and Phaeozems. The experiments utilized two tillage practices: conventional tillage (CT) and minimum tillage (MT) and four nitrogen treatment levels: no nitrogen, 46 kg N ha−1 combined with 10 t compost ha−1, 20 t compost ha−1, and 92 kg N ha−1. These treatments were arranged in a randomized complete block design with split plots, replicated three times. Overall, the results showed that ST, tillage method, and nitrogen fertilization had significant effects on nutrient stocks, maize yield, and nitrogen utilization efficiency. The highest maize grain yields, nitrogen use efficiency, and soil nutrient stocks were recorded in Phaeozems with MT and integrated N‐fertilization. In contrast, the lowest maize yields and nitrogen use efficiency were found in unfertilized plots of Cambisols under CT. The findings highlight the beneficial impact of MT and integrated nutrient management on enhancing nutrient stocks, yields, and nitrogen utilization efficiency across different STs, thereby supporting sustainable maize production.